THE MOBILE EMERGENCY SERVICE NURSING TEAM'S KNOWLEDGE OF STANDARD PRECAUTIONS - Isabel Karolyne Fernandes Costa; Glaucea Maciel de Farias; Allyne Karlla Cunha Gurgel; Karolina de Moura Manso da Rocha; Mirna Cristina da Silva Freitas; Amanda Alves Miranda De Souza (Universidade Federal do Paraná, 2012)
This exploratory, descriptive study aimed to discern what the nursing professionals of the Municipal Emergency Service of the metropolitan region of Natal in the state of Rio Grande do Norte knew about standard precautions. Data was collected by means of a structured instrument in the period of November - December 2010 and was organized and analyzed with the help of Statistics 6.0 and Microsoft-Excel XP. Of the 66 people who participated in the research, 16.67% were nurses, and 83.33% were nurse-technicians, mainly women between 41 and 50 years old. The majority had had no further in-service training and had worked in the emergency service for between one and four years. 66.67% responded incorrectly when questioned about the importance of standard precautions. It is important to disseminate the principles of standard precautions, bearing in mind that they should guide professional practice and that they contribute to safety by avoiding wounds and the sequelae of occupational exposure to biological matter.